A retrospective case comparison study of the relationship between an Integrated Care Pathway for people diagnosed with schizophrenia in acute mental health care and service users' length of stay, readmission rates and follow‐up within 7 days of discharge. Issue 6 (August 2017) - Attfield, J.; Brown, S.; Carter, T.; Callaghan, P.
Accessible summary: What is known on the subject?: There is some evidence reporting the value of diagnostic‐driven Integrated Care Pathways (ICPs) in reducing service users' length of inpatient stay, readmission rates and follow‐up within seven days of discharge, but this evidence is untested in studies comparing care using ICP with other forms of care planning. What this study adds to existing knowledge?: This study present findings from research comparing care in a Trust that uses an ICP with a Trust using another form of care planning to direct the care of people diagnosed with schizophrenia. We were interested particularly in whether using an ICP was linked to length of inpatient stay, readmission rates and follow‐up care within seven days of discharge. The results compare ICP driven care with another form of care. This study adds to the international evidence by being among the first to compare empirically, outcomes in a mental health Trust using an ICP with a Trust not using an ICP to direct care. What are the implications for practice?: Mental health nurses are central to the delivery of the psychosocial aspects of ICPs in particular and judging by the link between psychosocial interventions and quality of mental health care, it is possible that nurse‐led psychosocial interventions contributed to the reduced length of stay. Abstract: Background: Integrated Care Pathways (ICPs) are used to deliver mental health services, yet evidence relating to outcomes is mixed. Aim: To compare service users' length of stay, readmission rates and follow‐up within 7 days of discharge in a mental health Trust using an ICP to direct the care of people diagnosed with schizophrenia with a Trust using a nonICP method of care planning in England.Method: A cohort study with a random sample of 400 service users with outcomes analysed retrospectively. Results: The ICP Trust had a 13.5 day shorter average length of stay, this difference was statistically significant. No statistically significant differences were observed in rates of readmission or follow‐up within 7 days of discharge. Discussion and implications: Mental health nurses are central to the delivery of the psychosocial aspects of ICPs in particular and judging by the link between psychosocial interventions and quality of mental health care, it is possible that nurse‐led psychosocial interventions contributed to the reduced length of stay.